Corn starch ferulates with antioxidant properties prepared by N, N′-carbonyldiimidazole-mediated grafting procedure. (1st October 2016) - Wen, Yu; Ye, Fayin; Zhu, Jianfei; Zhao, Guohua
Highlights: A novel method for preparing corn starch ferulates. Reaction parameters were optimized by response surface methodology. Corn starch ferulates were found to exhibit the DPPH radical scavenging effects. The DS value of the products has a positive impact on the antioxidant activity. Abstract: This work presents novel synthesis processes and properties of corn starch ferulates. First, N, N ′-carbonyldiimidazole, a green activating reagent, was used to transform ferulic acid into ferulate-imidazolide. The ferulate-imidazolide was then further reacted with corn starch to produce corn starch ferulates. The grafting reaction of ferulic acid onto corn starch was confirmed by FT-IR and 1 H NMR. The degree of substitution (DS), relating products and reaction parameters, depended on the molar ratio of the anhydroglucose unit to ferulic acid ( n AGU/FA ), the temperature of the reaction, and the time that elapsed. The dependence of the degree of substitution was optimized by response surface methodology. Results implied the greatest DS (0.389) was obtained under the conditions of n AGU/FA 1:3.6, 90 °C and 7.12 h. The morphological, crystalline, and in vitro antioxidant properties were evaluated. The DPPH radical scavenging activity, reducing power, and ferric reducing power of the corn starch ferulates showed potential for antioxidant properties.